Performance Comparison Of Self Aeration Flotation Machine Vs Induced Air Flotation Machine With The Additional Effect Of Variation Of SiBX Dosage On % Recovery of Cu and Au At North Concentrator PT. X Papua - Putra, Budhi; M. Soedarsono, Johny Wahyuadi; Ariyani, Ira (Rekayasa Material, Manufaktur dan Energi, 2024)
Comparison of the performance of self aerating vs induced water flotation machines with the effect of adding SiBX dose variations on % recovery of Cu and Au, so that it can be carried out to optimize the recovery process of Cu and Au at PT. X Papua. It was carried out at the Cl concentrator plant scale, using three types of SiBX dosage variations, namely 5 g/t, 10 g/t, and 15 g/t which were applied to both types of flotation machines. Furthermore, mineral assay and XRD tests were carried out. The results of % recovery of Cu and Au as a whole show that the self aerating flotation machine is able to remove Cu and Au more effectively than the water induced flotation machine for all coarse, medium, and fine mineral size fractions. Recovery of Cu and Au is influenced by the hydrodynamic properties of the two types of engines. The effect of adding variations in SiBX doses was less significant on % recovery of Cu and Au.